2017
DOI: 10.1111/anae.13984
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial comparing real-time double-lumen endobronchial tube placement with the Disposcope® with conventional blind placement

Abstract: Double-lumen endobronchial tube placement is challenging. This study compared double-lumen tube placement with the Disposcope , a wireless videostylet allowing real-time visualisation, with conventional blind placement. Patients undergoing elective thoracic surgery with normal airways requiring one-lung ventilation were randomly allocated into two groups (27 patients in each group). The Disposcope was used to assist left-sided double-lumen tube placement in one group, and conventional blind placement was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…A recent study reported a wireless video stylet allowing real‐time visualisation during double‐lumen tube placement. The authors found that the stylet could help correctly position the double‐lumen tube and also saved time .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported a wireless video stylet allowing real‐time visualisation during double‐lumen tube placement. The authors found that the stylet could help correctly position the double‐lumen tube and also saved time .…”
Section: Discussionmentioning
confidence: 99%
“…In trauma patients wearing a semi-rigid neck collar, the Disposcope endoscope demonstrated a promising ability to guide successful endotracheal intubation [6]. Another study showed that the Disposcope endoscope could also be applied successfully in double-lumen tube placement [7].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Kamburoglu et al [11] investigated the efficacy of conventional FOB versus DE for the confirmation of the correct position of the DLT and reported shorter confirmation time with DE. Similarly, Chen et al [12] compared conventional blind tube placement versus DE using DLTs and showed higher success rates and shorter duration of placement with DE.…”
Section: Discussionmentioning
confidence: 99%